Determinants of generalized herpes simplex virus-2 epidemics: the role of sexual partner concurrency. (May 2013) - Kenyon, C; Colebunders, R; Hens, N
Summary: Little is known as to why some populations develop generalized herpes simplex virus 2 (HSV-2) epidemics. Sexual network-level factors, such as the proportion of partnerships that run concurrently, are plausible explanations. In this ecological analysis, we used Spearman's correlation coefficients to assess if there is an association between population prevalence of point-concurrency and HSV-2 in a number of national and subnational populations. We found that there is an association between prevalence of point-concurrency and female HSV-2 prevalence between different countries (Spearman's rho = 0.715; P = 0.020), and within different races and ethnic groups within countries. In addition, there was a strong association between peak HIV and HSV-2 prevalence in 40–44-year-old women at an international level (Spearman's rho = 0.720; P = 0.0001). This could be indicative of populations with high HIV and HSV-2 prevalence rates having extensively connected sexual networks which puts them at increased risk of spread by both these sexually transmitted infections (STIs). No country with an HSV-2 prevalence of under 20% in their 20–24-year-old women had a generalized HIV epidemic. Thus, HSV-2 prevalence in adolescents may be a useful marker of how risky a local sexual network is for STI spread and may provide a useful early indicator of the success or failure of behavior change initiatives.